2020
DOI: 10.1515/jcim-2019-0331
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of Kapalbhathi pranayama on short term heart rate variability (HRV) in healthy volunteers

Abstract: ObjectivesKapalbhathi Pranayam (Kapal = forehead; bhati = shining) is a breathing exercise that has been practiced to cleanse the frontal brain in traditional practices like yoga. Still, there exists a dearth of literature on the effect of Kapalbhathi pranayama on physiological systems. So this present study was carried out to find the immediate effect of “kapalbhathi Pranayam” practice for the period of 5 min on cardiac autonomic function among the healthy volunteers.Materials and methodsApparently 50 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the current study of phasic HRV, it was found that during pre-WM and KBH, there was parasympathetic withdrawal, and during post-WM after KBH practice, parasympathetic activity was reestablished, and the participants' accuracy improved. The findings of this study are consistent with a previous study, which found that KBH practice has a parasympathetic shifting effect [20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study of phasic HRV, it was found that during pre-WM and KBH, there was parasympathetic withdrawal, and during post-WM after KBH practice, parasympathetic activity was reestablished, and the participants' accuracy improved. The findings of this study are consistent with a previous study, which found that KBH practice has a parasympathetic shifting effect [20].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study investigated the immediate effect of KBH on short-term HRV in healthy participants. This study showed that there was parasympathetic withdrawal immediately after the KBH practice, while after the 20-minute recovery period, there was parasympathetic dominance [ 20 ]. The findings suggested that KBH had a parasympathetic shifting effect, and scientific evidence indicates that the parasympathetic shift of HRV promotes good cardiac health and lowers the risk of sudden cardiac death [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 20 21 ] The reduction in sympathetic activity causes decreased catecholamine secretion. [ 22 ] This improves peripheral circulation by increasing the peripheral vascular dilatation resulting in reduced DBP. [ 23 ] A Study done by Madanmohan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yoga has demonstrated its efficacy and affordability as an intervention in healthcare, suggesting its potential to alleviate the burden of cardiovascular diseases [5]. Many yoga practices, including slow breathing and meditation, can stimulate the parasympathetic nervous system, enhancing heart rate variability and contributing to improved vascular tone [6]. It's important to highlight that yoga practices have demonstrated comparable or superior efficacy to exercise in enhancing various health outcomes, including autonomic function, antioxidant status, stress, and patientreported outcomes [7].…”
Section: Introductionmentioning
confidence: 99%